ANALYSIS OF VARIATION OF SOUND CHANGES IN ARABIC LANGUAGE PHONEMES IN JUNIOR HIGH SCHOOL STUDENTS IN JAVA, INDONESIA (Universitas Negeri Semarang, 2023)
The purpose of this study was to determine the variation of Arabic sounds pronounced by 8th-grade junior high school students in Java, Indonesia. The method used in this study uses a qualitative method with descriptive analysis with the research subject of 8th-grade junior high school children in Java, Indonesia. The results of the study found variations in sound changes in 8th-grade middle school children in Java, Indonesia.